What factors predict faculty engagement in business ethics education?. Issue 7 (3rd October 2022) - Beauvais, Laura; Bosco, Susan; Desplaces, David; Kay, Avi
Abstract: Business ethics is widely viewed as essential to business education. However, considerable discretion exists regarding its actual instruction. This study explored the impact of instructor and institutional factors on faculty engagement with business ethics. A positive correlation emerged between belief in the importance of and comfort with teaching ethics and faculty engagement. Also, faculty in institutions without codes of ethics were more likely to address ethical behavior in the classroom. Finally, there was marginal support for a relationship between faculty perception of the importance of ethical behavior for career advancement and addressing ethical conduct in courses. Findings and their implications are addressed.